Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Badan Kepegawaian dan Sumber Daya Manusia Kota Tangerang Selatan - Siti Holillah; Zulkifli Rangkuti; Nurwulan Kusuma Devi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Employee performance in public sector institutions remains a critical issue, particularly in ensuring effective human resource management. Although the institutional performance of the Personnel and Human Resources Agency of South Tangerang City has been categorized as good, several performance indicators still require improvement. This study aims to examine the influence of work motivation and work discipline on employee performance. A quantitative approach with an associative design was employed. The population consisted of 33 employees from the Human Resource Competency Development Division, and all members were selected using a census sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 26. The results indicate that work motivation has a positive and significant effect on employee performance (t = 3.638; p < 0.05). Work discipline also shows a positive and significant effect (t = 5.137; p < 0.05). Simultaneously, both variables significantly influence employee performance (F = 57.187; p < 0.05), indicating that higher levels of motivation and discipline contribute to improved performance. These findings highlight the importance of strengthening motivational strategies and consistent disciplinary policies to enhance sustainable employee performance in public organizations.